Direct Imaging of Lipid Metabolic Changes in Drosophila Ovary During Aging Using DO-SRS Microscopy - Li, Yajuan; Bagheri, Pegah; Chang, Phyllis; Zeng, Audrey; Hao, Jie; Fung, Anthony; Wu, Jane Y.; Shi, Lingyan (Frontiers in Aging, 2022)
Emerging studies in the past decades have shown that lipid metabolism plays a versatile role in various aspects of aging. High resolution in situ optical imaging provides a powerful approach to study the metabolic dynamics of lipids, as well as protein, inside cells and tissues during the aging processes. Here, we integrated D2O probing with Raman and stimulated Raman scattering (DO-Raman/SRS) microscopy to directly visualize metabolic changes in aging Drosophila ovary. The sub-cellular spatial distribution of de novo protein synthesis and lipogenesis in ovary was quantitatively imaged and examined. Our Raman spectra showed protein-enriched early stages follicle were transformed to lipid-enriched mature eggs during oogenesis. DO-SRS imaging measured a higher protein synthesis in the earlier developing stages, while an increased lipid turn over at the late stage. Aged (35-day) flies had a dramatic decrease in metabolic turnover activities of both protein and lipids. and a significantly lower level of saturated and unsaturated lipids, particularly, in the germ stem cell niche of germarium, which suggested that lipids may function in stem cell maintenance and division. We further found an ectopic accumulation of unsaturated lipids in the germ cells (nurse cell and oocytes) localized regions in 35-day old flies, which suggests that unsaturated lipids may play an important role in the processes of oocyte maturation. The abnormal lipid translocation indicated that the lipid trafficking between somatic and germ cells in the old flies was disrupted, leading to the loss of cellular metabolic homeostasis in old fly ovaries. The aberrant mitochondrial morphology and atypical accumulation of Cytochrome c observed in our study provide the evidence for this dysregulation of metabolic homeostasis. As far as we know, this is the first study that directly visualizes spatiotemporal transformations of lipid (and protein) metabolism in Drosophila ovary during development and aging processes. Our study not only demonstrates a new imaging platform for visualizing metabolic dynamics of lipids and protein in situ but also unravels how the metabolic activity and distribution of lipids changes in Drosophila ovary during aging.